ANALISIS PENGARUH PENGEMBANGAN UMKM DALAM MENGETASKAN KEMISKINAN - Yuyun Fitria (Universitas Mitra Indonesia, 2023)
The purpose of this study was to determine the influence of MSMEs in alleviating poverty in Indonesia. The data used in this study were secondary data. Furthermore, the data collection techniques used in this study were taken based on data from the Central Statistics Agency (BPS) to collect data. In this research This method uses the classic assumption test method and hypothesis testing with the help of the eviews version 10 program. Based on the regression results, the regression coefficient for the MU variable shows a positive sign, which is equal to -23.72. Based on the partial significance test, the effect of the MU variable on reducing poverty in Indonesia shows an insignificant number. This is indicated by the tcount value of the MU variable of 0.501 which is smaller than the ttable value of 2.35336 with a 95% confidence level (α = 0.05). Thus UM has a positive effect on poverty alleviation. This means that with an increase in the MW of 23.72 percent, it will result in reducing poverty by 0.501 percent assuming cateris paribus. Keywords :Micro, Small and Medium Enterprises (UMKM) and Poverty